2011
DOI: 10.1155/2011/129727
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Calcium Phosphate Bioceramics for Orthopaedic Reconstructions: Clinical Outcomes

Abstract: BCP are considered the most promising biomaterials for bone reconstruction. This study aims at analyzing the outcomes of patients who received BCP as bone substitutes in orthopaedic surgeries. Sixty-six patients were categorized according to the etiology and morphology of the bone defects and received scores after clinical and radiographic evaluations. The final results corresponded to the combination of both parameters and varied from 5 (excellent result) to 2 or lower (poor result). Most of the patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 34 publications
0
48
0
4
Order By: Relevance
“…Calcium phosphates and biphasic calcium phosphate ceramics can be candidate for the bone-scaffold and restorative dentistry [129][130][131][132][133][134][135] . Calcium phosphate based coatings have been developed and used in clinical dentistry and medicine [136][137][138] .…”
Section: Calcium Phosphates As Biomedical Applications and Food Additmentioning
confidence: 99%
“…Calcium phosphates and biphasic calcium phosphate ceramics can be candidate for the bone-scaffold and restorative dentistry [129][130][131][132][133][134][135] . Calcium phosphate based coatings have been developed and used in clinical dentistry and medicine [136][137][138] .…”
Section: Calcium Phosphates As Biomedical Applications and Food Additmentioning
confidence: 99%
“…Previous studies showed that BCP comprising approximately 60% HA and 40% β-TCP allows control of resorption and maintenance of osteoconductive properties [11,12,13,14,15,16]. Several investigators found that the optimal macroporosity of this material for the ingrowth of bone tissue is between 150 and 500 μm [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore this material is often used in non-weight bearing areas or combined with other materials such as metals. In these locations BCP has successfully been used as bone filler in oral and maxillofacial, reconstructive and orthopedic surgeries 84 .…”
Section: Calcium Phosphatesmentioning
confidence: 99%
“…The weight of the porous constructs measured 60% +/-7% (n =6) of the solid grafts, resulting in average porosity of 40%. Cell viability of the printed constructs assessed by live/dead assay after 7 and 14 day of culture showed respectively for day 7 and 14: 90% (CI [85][86][87][88][89][90][91][92][93][94][95][96] and 79% (CI [73][74][75][76][77][78][79][80][81][82][83][84][85][86] for the porous control, 91% (CI 87-96) and 80% (CI for the porous with pBMP-2, and 85% (CI 81-89) and 69% (CI 59-78) for the solid constructs (Fig. 4).…”
Section: Printingmentioning
confidence: 99%